(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
We also analyzed numerous methods, approaches, and tools in this paper and compare their effect on the healthcare industry. The purpose of data mining is to translate statistics, numbers or texts into knowledge or information that can be interpreted by a machine. Its key goal is to build an automated method for defining and disseminating healthcare knowledge on data mining technologies in healthcare systems. The aim of this paper is to create a thorough research report on the numerous forms of data mining applications in the health sector and to reduce the scope of the healthcare data transaction review. In this study we have explained about the applications, challenges, techniques of data mining in health sector which is concluded that Data mining techniques are helpful to explore medical expertise in this situation, because it is quite fascinating. The findings of this analysis were found that a mixture of more than one data mining tool than a single diagnostic or predictive methodology may be more promising.